Analgesic efficacy of systemic ketamine and lignocaine for pre-emptive multimodal analgesia in dogs - Kaka, Ubedullah (2016)
Presently, there is no ideal analgesic protocol which is free of side effects to counteract central sensitisation and abolish pain in postoperative period. Opioids being frontline drugs for postoperative pain management possess clinically significant side effects such as respiratory depression, vomiting, bradycardia and vasodilation. Recent findings point towards preemptive multimodal analgesia as the way forward. Ketamine and lignocaine are two potential drugs to be incorporated to an opioid-based protocol, however, research related to their analgesic effects in dogs is limited. This study evaluated the analgesic effects of systemic ketamine and lignocaine for postoperative analgesia in dogs. Treatments were administered in a cross over design with one week wash-out period. Analysis was performed using SAS software package. Data were compared across treatments and time measurement using repeated- measures ANOVA model and paired T test where two treatments were compared. Non parametric tests were used when data were not normally distributed. In experiment one of this study, effects of ketamine and lignocaine on electroencephalography (EEG) with electric noxious stimulus under minimal anaesthesia model were studied. Ketamine at 3 mg/kg intravenous (IV), loading dose (LD) and constant rate infusion (CRI) of 10 and 50 μg/kg/min, and lignocaine at 2 mg/kg followed by 50 and 100 μg/kg/min significantly depressed the median frequency (MF) of EEG, an indicator of nociception. Corresponding serum concentrations at the points of testing that depressed MF were between 1898.41 ± 110.04 and 2100.59 ± 425.48 ng/ml for lignocaine and between 248.71 ± 75 and 641.35 ± 197 ng/ml for ketamine. In experiment two, an algometer was modified, validated and subsequently used to determine mechanical nociceptive thresholds in conscious dogs. In experiment three, ketamine alone at 0.5 mg/kg LD followed by CRI of 30 μg/kg/min and 50 μg/kg/min, and ketamine at 30 μg/kg/min with lignocaine at 2 mg/kg LD followed by 100 μg/kg/min significantly increased the mechanical thresholds during the periods of infusion. Corresponding serum concentrations of ketamine were found to be above 100 ng/ml. Thresholds returned to baseline within 20 minutes following cessation of infusion and serum concentrations were below 100 ng/ml. In experiment four, ketamine and lignocaine in addition to tramadol at 4 mg/kg premedication was evaluated for preemptive multimodal analgesia in dogs undergoing ovariohysterectomy. Results showed that the combination of ketamine-lidocaine-tramadol obtunded intra-operative sympathetic responses better than tramadol alone. The combination also attenuated primary hyperalgesia better than tramadol in the immediate 8 hours post-surgery, and tended to reduce secondary hyperalgesia during the 72-hour postoperative study period. In conclusion, systemic ketamine and lignocaine possess analgesic effects. Ketamine at serum concentrations of > 100 ng/ml provided analgesia. Ketamine at 0.5 mg/kg LD followed by CRI at 30 or 50 μg/kg/min combined with lignocaine at 2 mg/kg LD followed by 100 μg/kg/min, is safe for preemptive multimodal analgesia in dogs under anaesthesia. Preemptive infusions of ketamine and lignocaine in addition to tramadol augmented analgesia, likely, by attenuating intra-operative nociceptive inputs and reducing central sensitisation.